Analysis of Learning Agility on Employees’ Technostress in Using the Sinergy Boma Application in the Bojongmangu District Office, Bekasi Regency - Nurhalimah; Uus Mohammad Darul Fadli; Ery Rosmawati (Research in Management of Technology and Business, 2025)
The development of technology in the government sector requires employees to adapt to digital systems, but this also has the potential to cause technostress. This study aims to analyze the effect of learning agility on technostress in Bojongmangu District employees in using the Sinergy BOMA application. This research design uses a qualitative method to describe the phenomena that exist in the Bojongmangu District Office, Bekasi Regency. The population is all sample district employees consisting of finance, personnel, and three staff sections with five informants selected purposively. Data were collected through in-depth interviews and participatory observations and analyzed interactively with several employees to understand their experiences in adapting to technology. The results showed that employees with high learning agility were more adaptable, found solutions independently, and had lower levels of technostress. Conversely, employees with low learning agility were more susceptible to work pressure due to difficulty in understanding application features. Therefore, the development of learning agility is an important strategy in reducing technostress and increasing work effectiveness in a digital environment.